L’identità femminile nell’«Amica geniale» di Elena Ferrante e nel romanzo «Al-bab al-maftuh» [La porta aperta] di Latifa al-Zayyat - Wardshan Moustafa Ahmed Abdelrahman (Culture e Studi del Sociale)
Starting from the assumption that socio-cultural changes have an impact on the formation of women's identities, this article explores the construction of female identities in Egypt and in Italy from a cultural perspective. This perspective analyzes texts in relation to socio-cultural changes that have occurred over time and allow people to rethink the concept of women's identity, comparing styles and cultural differences between Elena Ferrante (1943) and La??fa al-Zayy?t (1923 –1996). The first section of this work focuses on the perspective of Elena Ferrante, analyzing the conflict between the traditional woman and the intellectual woman in the Neapolitan cycle of My Brilliant Friend (2011-2014) and explores the identity of woman in the light of condition of Italian women in the second half of the 20th century up to the present days. The second section focuses on the conception of women's identity and family in Egypt in the first 20th century, referring to the historical novel al-B?b al-maft?? (1960, The Open Door) and focusing mainly on the struggle for the affirmation of women’s right and what this coincides with the liberation of the country from colonialism. The final results of the comparison are highlighted in the conclusion.